2014
DOI: 10.1007/s00441-014-1926-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and evaluation of mesenchymal stem cells derived from human embryonic stem cells and bone marrow

Abstract: Embryonic stem cells (ESCs) and mesenchymal stem cells (MSCs) have been studied for years as primary cell sources for regenerative biology and medicine. MSCs have been derived from cell and tissue sources, such as bone marrow (BM), and more recently from ESCs. This study investigated MSCs derived from BM, H1- and H9-ESC lines in terms of morphology, surface marker and growth factor receptor expression, proliferative capability, modulation of immune cell growth and multipotency, in order to evaluate ESC-MSCs as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 58 publications
7
39
0
3
Order By: Relevance
“…Various groups have previously documented the increased proliferative potential of PSC‐MSCs in comparison to BM‐MSCs but we are the first to compare PSC‐MSCs to fetal MSCs. We observed that ES‐MSCs proliferate at an increased rate in comparison to amniotic fluid‐derived MSCs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Various groups have previously documented the increased proliferative potential of PSC‐MSCs in comparison to BM‐MSCs but we are the first to compare PSC‐MSCs to fetal MSCs. We observed that ES‐MSCs proliferate at an increased rate in comparison to amniotic fluid‐derived MSCs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Using these cells also avoids the ethical ambiguities like using embryonic stem cells. 17 Several previous studies also demonstrated that mesenchymal stem cells could recruit to injured tissue and generate high levels of cytokines and growth factors 18,19 and play a repair role. Therefore, it is interest to determine whether MSCs can be tracked in vivo with non-invasive imaging after AKI stem cells treatment, which will provide a tool for the development and testing of optimal AKI-specific treatment protocols.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the differentially expressed genes were highly dissimilar with very less overlap (5% -16%) among the three sources. and had a higher capability of immunomodulation, but were less inducible for differentiation as compared to the BM-MSCs [35].…”
Section: Discussionmentioning
confidence: 99%